The blood-brain barrier, cancer, cell phones, and microwave radiation. - Lin, James C. (IEEE Antennas & propagation magazine.)
The blood-brain barrier is an anatomic/physiologic complex associated with the cerebral vascular system. It is composed of a network of astrocytic pseudopodia, which envelopes the tight junctions of the vascular endothelium. It is a natural defense system, which maintains the physiochemical environment of the brain within certain narrow limits that are essential for life. The effect on this system of microwave radiation from cell phones is discussed together with the use of microwave radiation in the treatment of tumors.